Pelatihan Efisiensi Sumber Daya Sistem Operasi Windows pada Masa Pandemi Covid 19 - Aryotejo, Guruh; Hakim, Muhammad Malik; Firmansah, Fery; Safarizki, Hendramawat Aski (Universitas Nusantara PGRI Kediri, 2021)
The Ministry of Education and Culture is implementing online learning as a learning method of choice during this pandemic. The obstacle that is often faced in terms of teaching media is the inadequate specification of a computer or laptop for online learning, especially in terms of operating systems that do not match the specifications of a computer or laptop. The objective of this community service is to increase the ability of educators and the general public to optimize the Windows 10 operating system on a computer or laptop with minimal specifications. This community service was carried out by organize an online training using Zoom. The result shows that online training participants are able to optimize Windows 10 on their respective hardware. This shows that the participants already understand how to optimize Windows 10 in the minimum computer or laptop specifications.